Resource recovery from food-processing wastewaters in a circular economy: a methodology for the future - Durkin, Alex (2023)
Food-processing wastewater (FPWW), as opposed to solid residues, occurs extensively throughout the world, and has considerable potential for resource recovery (RR), however, at present, it is severely underutilized. This paper serves as a suggested 'plan forward' to optimize integrated RR from FPWW. In order to optimize this potential and 'close the loop', there needs to be further development in in-depth analytical methods of the FPWW; axenic/mixed cultures or microbial communities capable of growing on FPWW and hence producing single-cell protein for animal feed and food additives; cost-effective methods for separating high-value-added solutes such as vitamins K2, B12, and B2; isoflavones and flavanones; integrated energy- and water-recovery flowsheets; and optimization methods to integrate RR and energy harvesting with minimal impact on the environment. Each of these areas is examined and future research directions are laid out.